Konstruksi sosial makna Tari Gandrung Seblang bagi Desa Bakungan Kecamatan Glagah Kabupaten Banyuwangi - Heri Setiawan; Sukamto Sukamto; I Dewa Putu Eskasasnanda; I Nyoman Ruja; Ratih Pramesthi (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
The formulation of the problems in this study are (1) What is the history of the emergence of the Gandrung Seblang Dance tradition in Bakungan Village, Glagah District? (2) What is the form of the Gandrung Seblang Dance and the meaning contained in the Gandrung Seblang Dance tradition in Bakungan Village, Glagah District? (3) How is the Social Construction of the Gandrung Seblang Dance in Bakungan Village, Glagah District? This study used a qualitative approach with a descriptive research type. The data collection technique uses a purposive technique. The results of the study show that: (1) There are two versions of the history of the creation of the Gandrung Seblang dance in the Bakungan community. The first version states that this tradition began as a ritual to honor the services of Mbah Djoyo, a village ancestor and to express gratitude to the village guard who was willing to be transferred for the development of the village area. The second version states that the Gandrung Seblang dance arose as a result of an ancient story in which many residents of Bakungan Village experienced disease outbreaks and crop failures. The researcher suggests researching "The Development of the Gandrung Dance Tradition in the Millennial Era" from a different theoretical perspective, besides that future researchers can also use research methods that are different from this research. Rumusan masalah dalam penelitian ini adalah (1) Bagaimana sejarah munculnya tradisi Tari Gandrung Seblang di Desa Bakungan Kecamatan Glagah? (2) Bagaimana Bentuk Tari Gandrung Seblang dan makna yang terkandung dalam tradisi Tari Gandrung Seblang di Desa Bakungan Kecamatan Glagah? (3) Bagaimana Konstruksi Sosial Tari Gandrung Seblang di Desa Bakungan Kecamatan Glagah?. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Teknik pengambilan data menggunakan teknik purposive. Hasil penelitian menunjukkan bahwa: (1) Terdapat dua versi sejarah terciptanya tari Gandrung Seblang di masyarakat Bakungan. Versi pertama menyatakan bahwa tradisi ini bermula sebagai ritual untuk menghormati jasa Mbah Djoyo, seorang leluhur desa dan rasa terima kasih kepada dayang penunggu desa yang berkenan dipindahkan guna pembangunan wilayah desa. Versi kedua, menyatakan bahwa tari Gandrung Seblang muncul akibat kisah zaman dahulu dimana banyak penduduk Desa Bakungan mengalami wabah penyakit dan kegagalan panen. Peneliti menyarankan untuk meneliti “Perkembangan Tradisi Tari Gandrung di Era Milenial” dalam perspektif teoretik yang berbeda, selain itu peneliti selanjutnya juga bisa menggunakan metode penelitian yang berbeda dengan penelitian ini.